Recent Advances in Nanoplatforms for the Treatment of Osteosarcoma - Wu, Kunzhe; Yu, Beibei; Li, Di; Tian, Yangyang; Liu, Yan; Jiang, Jinlan (Frontiers in Oncology, 2022)
Osteosarcoma (OS) is the most common primary bone tumor in children and young people. Traditional surgical excision combined with chemotherapy presents many limitations, such as resistance and systemic side effects of chemotherapy drugs, postoperative recurrence, and bone defects. Given these limitations, novel therapeutic modalities for OS treatment using nanometer-sized platform-based chemotherapeutic delivery have emerged as a promising alternative therapy. This form of therapy offers multiple advantages, such as accurate delivery of the drug to the tumor site and repair of limited bone defects after tumor resection. In this review, we briefly summarize nanoplatforms, including liposomes, polymeric nanoparticles, inorganic nanoparticles, nanomicelles, dendrimers, nanocapsules, and exosomes. The essential shortcomings involved in these nanoplatforms, such as poor stability, immunogenicity, insufficient circulation, and drug leakage are also discussed, and related solutions are briefly proposed. Finally, the application prospects of nanoplatforms in the treatment of OS are discussed.